Brazil : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2015)
This Selected Issues paper examines infrastructure investment in Brazil. Brazil has inferior overall infrastructure quality relative to almost all its export competitors. Brazil's infrastructure endowment ranks low by international standards, and its low quality affects productivity, market efficiency, and competitiveness. Areas in which Brazil's competitiveness has lagged include, but are not limited to, education, innovation, governance, and justice. Brazil's infrastructure gap has become a major obstacle to growth and filling this gap will entail increasing investment and also stepping up other reforms.